Multi-wavelength switchable random fibre laser based on double Sagnac-loop filter. Issue 17 (7th October 2021) - Pan, Honggang; Guo, Taotao; Zhang, Ailing; Liu, Chang
Abstract : A multi-wavelength switchable random fibre laser based on a double Sagnac-loop filter is proposed. The threshold of laser is 27 mW and the slope efficiency of the total power output to pump power is about 0.04%. In the experiment, stable and switchable laser outputs of single-, dual-, tri- and quad-wavelength channels are obtained by adjusting the polarization controller at room temperature. The wavelength positions are tuneable within the range of 1556–1564 nm and intervals are switchable between 2.5, 5 and 7.5 nm. Under 300 mW pump power, average power intensity of −24dBm is achieved. Furthermore, the output of fibre laser is relatively stable with less than 0.2 nm wavelength drift and less than 1.5 dBm power fluctuation within one hour. The proposed random fibre laser has promising application prospects for distributed sensing systems and biomedical imaging.